Gender differences in the experience of interstitial cystitis/bladder pain syndrome - Windgassen, Sula S.; Sutherland, Susanna; Finn, Michael T. M.; Bonnet, Kemberlee R.; Schlundt, David G.; Reynolds, W. Stuart; Dmochowski, Roger R.; McKernan, Lindsey C. (Frontiers in Pain Research, 2022)
Aims This study assessed gender differences in a debilitating urologic pain condition, interstitial cystitis/bladder pain syndrome (IC/BPS). We aimed to (1) evaluate how pain, symptom, and distress profiles of IC/BPS may differ between genders and (2) obtain in-depth firsthand accounts from patients to provide additional insight into their experiences that may explain potential gender differences. Methods A mixed methods approach combined validated patient-reported outcome measures with a single timepoint 90-min focus group. Tests of summary score group differences between men and women were assessed across questionnaires measuring urologic symptoms, pain, emotional functioning, and diagnostic timeline. Qualitative analysis applied an inductive-deductive approach to evaluate and compare experiences of living with IC/BPS Group narratives were coded and evaluated thematically by gender using the biopsychosocial model, providing insight into the different context of biopsychosocial domains characterizing the male and female experience of IC/BPS. Results Thirty-seven participants [women (n = 27) and men (n = 10)] completed measures and structured focus group interviews across eight group cohorts conducted from 8/2017 to 3/2019. Women reported greater pain intensity (p = 0.043) and extent (p = 0.018), but not significantly greater impairment from pain (p = 0.160). Levels of psychological distress were significantly elevated across both genders. Further, the duration between time of pain symptom onset and time to diagnosis was significantly greater for women than men (p = 0.012). Qualitative findings demonstrated key distinctions in experiences between genders. Men appeared not to recognize or to deter emotional distress while women felt overwhelmed by it. Men emphasized needing more physiological treatment options whilst women emphasized needing more social and emotional support. Interactions with medical providers and the healthcare system differed substantially between genders. While men reported feeling supported and involved in treatment decisions, women reported feeling dismissed and disbelieved. Conclusion The findings indicate different pain experiences and treatment needs between genders in persons experiencing urologic pain and urinary symptoms, with potential intervention implications. Results suggest gender health inequality in medical interactions in this urologic population needing further investigation.